Leveraging Prototype Method for Designing Tajweed Mobile Based Learning - Muhammad Azzam Izzuddin; Andri Andri; Hardiyansyah Hardiyansyah (Journal of Information System and Informatics, 2023)
In today's fast-paced society, individuals often struggle to find dedicated time for studying the Qur'an. This research aims to address this challenge by designing and developing a Mobile-Based Tajweed Learning Application. By harnessing the power of mobile devices, this application provides users with a platform for independent and accurate Tajweed Science learning. To bridge the gap between developers and users, the Prototype Method is employed in the development process. This collaborative approach offers several benefits, including concept testing, cost and time savings, increased user involvement, iterative improvements, risk reduction, and enhanced communication. By actively involving users throughout the development cycle, the application can better align with their requirements and expectations, leading to an improved end product. The effectiveness and reliability of the mobile-based Tajweed learning application are rigorously validated through black box testing. This thorough testing method ensures that the application functions as intended, delivering a seamless learning experience to users. Furthermore, the application leverages the Flutter framework, enabling optimal performance and responsiveness. The framework's features, such as hot reload, contribute to efficient development and ensure a smooth user experience. The results of the Tajweed Mobile Based Learning project demonstrate that the application effectively provides learning materials and facilitates practice sessions with ease. By utilizing this mobile application, users can access comprehensive Tajweed resources conveniently and independently, overcoming the time constraints often associated with studying the Qur'an. This research showcases the potential of mobile technology to enhance Quranic education and empower individuals in their Tajweed journey.